EFEKTIVITAS PROGRAM PENGEMBANGAN PEMBERDAYAAN MASYARAKAT PADA DINAS SOSIAL KABUPATEN PIDIE JAYA - Zulfikar Zulfikar; Rozaili Rozaili; Nurul Marjani (Jurnal Sosial Humaniora Sigli, 2023)
All over the world, the increase in population in developing and developed countries is accompanied by the same problem, namely a decrease in the level of public services for the community. The phenomenon of poverty in Indonesian cities like Papua is one example. Papua owns 26.80% West Papua 21.43% East Nusaa Tenggara 20.23% Malukui 16.23% Gorontalo 15.51% Aceh 14.75% and other cities One way to improve people's welfare is through community empowerment. This study found that the Pidie Jaya District Office of Social Affairs played an important role in empowering the community by changing the way people think. The Pidie Jaya District Office of Social Affairs itself has attempted to empower the community by offering assistance to economically disadvantaged communities. This type of descriptive research, a qualitative approach, is used in this study. The results of the study show that the community empowerment program used by the Pidie Jaya District Office is still ineffective. How big or small the program depends on the wishes and resources of the community. Therefore, to carry out the Community Empowerment Development Program, the government and the community must work well together. Lack of agreement among the community, ignorance about how to look after, lack of knowledge about how to use rocks, and a very low budget are some of the obstacles that have prevented this program from being implemented. The advice that can be given in this study is that the Social Service Office of Pidie Jaya Regency The effectiveness of the Community Empowerment Development Program in Pidie Jaya Regency needs to be continued, by using a dynamic empowerment process or adapting to the typology of community empowerment and after each completion of a series of activities the community empowerment development program needs to be evaluated towards the development of community empowerment.Keywords : Effectiveness, Program, Community Empowerment Development